2010
DOI: 10.3109/07420528.2010.497234
|View full text |Cite
|
Sign up to set email alerts
|

Chronotypes and Subjective Sleep Parameters in Epilepsy Patients: A Large Questionnaire Study

Abstract: Accumulating evidence suggests epilepsy and seizures may influence circadian rhythms and that circadian rhythms may influence epilepsy. It is also conceivable that seizure timing influences the timing of daily activities, sleeping, and wakefulness (i.e., chronotype). Only one group has studied the distribution of chronotypes of epileptics, showing significant differences between the diurnal activity patterns in two groups of patients with different epilepsy syndromes. The authors performed a questionnaire-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
34
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 42 publications
5
34
1
2
Order By: Relevance
“…Only GE patients reported more eveningness-preference than FE, which is consistent with a previous study (Pung and Schmitz, 2006). To support the reliability of circadian preference survey, we assessed mid-sleep time during workdays and free-days and calculated social jetlag in both PWE (GE vs. FE) and HC, similar to the previous two studies (Hofstra et al, 2010;Unterberger et al, 2015). Hofstra et al (2010) explained the discrepancies of findings between studies by the difference of age and sample sizes.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Only GE patients reported more eveningness-preference than FE, which is consistent with a previous study (Pung and Schmitz, 2006). To support the reliability of circadian preference survey, we assessed mid-sleep time during workdays and free-days and calculated social jetlag in both PWE (GE vs. FE) and HC, similar to the previous two studies (Hofstra et al, 2010;Unterberger et al, 2015). Hofstra et al (2010) explained the discrepancies of findings between studies by the difference of age and sample sizes.…”
Section: Discussionsupporting
confidence: 81%
“…JME patients showed more eveningness-preference compared to TLE patients in similar age groups. Hofstra et al (2010) found significant differences in morningness/eveningness distribution, timing of mid-sleep (corrected for sleep duration), and total sleep time on free days between epileptics and healthy controls. However, overall distributions of chronotypes and sleep parameters between the groups of patients with TLE, FLE, and JME did not differ.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations